Multinateral regime for foreign investment: an assessment of the emerging trends - Dhar, Biswajit; Chaturvedi, Sachin (New Delhi, 1998)
The present paper is an attempt to discuss the various issues that need to be considered while assessing the implications of the proposed investment regime from the viewpoint of developing countries. At the outset, the paper would discuss the OECD proposal for a Multilateral Agreement on Investment (MAI).
Keywords: Economic development